Understanding Inflation in Malawi : A Quantitative Investigation - Frank Wu, Dong. (Washington, D.C. : International Monetary Fund, 2017)
This paper focuses on the role of the pass-through of the exchange rate and policydeterminants in driving inflation. Using linear and nonlinear frameworks, the paper finds: (i) after the switch to a floating exchange rate regime in 2012, nonfood prices not only directly influence headline inflation, but also have an significant impact on food inflation via second round effects; (ii) the pass-through of the exchange rate to headline inflation has jumped from zero to 11 percent under the floating regime, after controlling for other factors; (iii) the improved significance of T-bill rates in shaping inflation flags its importance in Malawi's monetary framework although the monetary transmission mechanism needs further strengthening; (iv) the increased impact of broad money underscores the necessity for fiscal discipline and central bank independence.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet